Retroelement Insertion in a CRISPR/Cas9 Editing Site in the Early Embryo Intensifies Genetic Mosaicism - Jeehyun Jeon; Jeehyun Jeon; Jung Sun Park; Byungkuk Min; Sun-Ku Chung; Min Kyu Kim; Yong-Kook Kang; Yong-Kook Kang (Frontiers in Cell and Developmental Biology, 2019)
Continued CRISPR/Cas9-mediated editing activity that allows differential and asynchronous modification of alleles in successive cell generations expands allelic complexity. To understand the earliest events during CRISPR/Cas9 editing and the allelic selection among the progeny of subsequent cell divisions, we inspected in detail the genotypes of 4- and 8-cell embryos and embryonic stem cells (ESCs) after microinjection of a CRISPR toolkit into the zygotes. We found a higher editing frequency in 8-cell embryos than in 4-cell embryos, indicating that the CRISPR/Cas9 activity persisted through the 8-cell stage. Analysis of a CRISPR/Cas9 transgenic founder mouse revealed that four different alleles were present in its organs in different combinations and that its germline included three different mutant alleles, as shown by the genotypes of the pups. The indel depth, which measured the extent of indels at the sequence level within single embryos, decreased significantly as the embryos advanced to form ESCs, suggesting that exclusion of fatal indels occurred in the subsequent cell generations. Interestingly, we discovered that the CRISPR sites frequently contained introduced retroelement sequences and that this occurred preferentially with certain classes of retroelements. Therefore, in addition to CRISPR/Cas9's innate mechanism of separate, differential enzymatic modifications of alleles, the frequent retroelement insertions that occur in early mouse embryos during CRISPR/Cas9 editing further expand the allelic diversity and mosaicism in the resulting transgenic founders.